Kegiatan Sosial Kesehatan Masyarakat dalam Program “Gerakan Kaki Seribu Chandra Lukita” bagi Masyarakat Penyandang Disabilitas di Indonesia - Chandra Lukita; Taufan Hunneman; Amroni Amroni; Marsani Asfi; Petrus Sokibi; Yuni Awalaturrohmah Solihah; Wiwiek Nurkomala Dewi; Agus Sevtiana (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2021)
In Indonesia, like many other developing countries, there are still many individuals who have lost their legs or have serious leg problems due to various reasons, such as accidents, illnesses or congenital conditions. The main focus of this activity is providing orthopedic assistance/prosthetic limbs to people in need. The aim of this activity is to improve the health and welfare of people with disabilities through a program called "Gerakan Kaki Seribu Chandra Lukita". The method of community service activities consists of socialization, patient registration and examination, making orthopedic equipment, installing equipment and monitoring and evaluating activities. The result of this activity is an improvement in general health status among people with disabilities, including increased access to needed health services.